Mepyramine maleate treatment of urticaria in horses; a multi-centered, randomized, placebo controlled, double blinded clinical trial - Ural, Kerem; Ulutas, Bülent (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The aim of the present study was to investigate the efficacy of mepyramine maleate in horses with urticaria. A total of 31 horses, between the ages of 1 and 8 years, were enrolled and randomly assigned to either a placebo or an intramuscular mepyramine maleate group. Clinical evaluations were done by the same investigator, who scored clinical healing, throughout the study and was blinded to the allocation to the groups. At the end of the trial, mepyramine maleate treatment significantly decreased (P